From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Un projet participatif sur la réduction de la pollution atmosphérique dans quatre pays de l’Afrique de l’Ouest : quel rôle pour les femmes ? - Saint-Charles, Johanne; Yates, Stéphanie; Kêdoté, Nonvignon Marius (Recherches participatives et équité en santé, 2022)
C echapitreportesurlesdéfisd’uneapprocheparticipativeintégrant une perspective d’équité de genre rencontrés dans le cadre d’un programme de recherche-intervention sur la pollution urbaine en Afrique de l’Ouest, programme intitulé « Chaire écosanté sur la pollution urbaine de l’air et les maladies respiratoires1 ». Conçu et dirigé par des chercheurs et chercheuses de quatre pays africains (Bénin, Burkina Faso, Côte d’Ivoire et Sénégal), ce programme regroupait des équipes derecherchedechacundespays(équipes-pays)etquelquescollèguesde«paysdunord»,dontleCanada(Québec).IlaétéfinancéparleCentre de recherches pour le développement international du Canada. Outre des objectifs de recherche et de formation, la Chaire comportait un volet nommé Air-Sain qui visait à sensibiliser les actrices et acteurs dediversmilieuxetàsoutenirdeschangementsdurablesafinderéduirela pollution urbaine.
Keywords: 2000 à aujourd'hui; afrique; afrique de l'ouest; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques

Capital, labor, and gender: The consequences of large-scale land transactions on household labor allocation - Hajjar, Reem; Ayana, Alemayehu N.; Rutt, Rebecca; Hinde, Omer; Liao, C.; Keene, Stephanie; Bandiaky-Badji, Solange; Agrawal, Arun (Journal of Peasant Studies, 2020)
Contemporary large-scale land transactions (LSLTs), also called land grabs, are historically unprecedented in their scale and pace. They have provoked robust scholarly debates, yet studies of their gender-differentiated impacts remain more rare, particularly when it comes to how changes in control over land and resources affect women's labor, and thereby their livelihoods and well-being. Our comparative study of four LSLTs in western Ethiopia finds that the transactions led to substantial land use change, including relocation and decrease in size of smallholder parcels, loss of communally-held grazing lands, and loss of forests. These changes had far-reaching impacts on household labor allocation, the gendered division of labor, and household wellbeing. But their effects on women are both more adverse and more severe, expressed in terms of increased wage labor to make up for lost land and livestock, more time spent gathering firewood and water from increasingly distant locations, and an increased intensity of household responsibilities where male members underwent wage labor migration. These burdens led to negative psychological, corporal, and material effects on women living in and near transacted areas compared to their situation prior to transactions. This article both responds to the deficit in studies on the impacts of LSLTs on gendered livelihoods, labor relations, and wellbeing outcomes, and lays the groundwork for future research. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; agriculture; approches et analyses; environnement; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie

Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques